Detection of Sero-positive Anti- toxoplasmosis Anti-bodes IgG among Women in Baghdad Province - Abdullah Abbas Hamzah; Qater Al-Nada Ali Kanaem ALIbady (Institute of Medico-legal Publications Pvt Ltd, 2021)
A total of 83 serum samples were randomly collected from different centers in Baghdad province, the resultsrecorded in this study which started in July 2018 until the end of November 2018, by using one technique,method ELISA. The results were showed increased the percentage of seropositive anti- toxoplasmosis IgGantibodies at age groups 20 – 29 years, which were 23.9% among women infected with toxoplasmosiscomparative with other age groups. Also showed increase the percentage of sero-positive anti- toxoplasmosisIgG Abs in urban which were 42.9% comparative with rural, which were 8.0%. Also occur increasedsignificantly in percentage IgG Abs in serum of affected women with toxoplasmosis in first and secondmonth from abortion period, which were respectively 17.8% and 16.0%. So increase these antibodies(Abs) in serum of infected women with this disease in 1st trimester period comparative with other months.Therefore so it was necessary to use of early diagnosis for pregnant infected women with toxoplasmosis.